Mode choice to school in Selangor - Jamaludin, Nurul Huda; Syed Mohamed Rahim, Sharifah Allyana; Harun, Nur Zarifah; Roslan, Azzuhana; Jamaluddin, Askiah (Malaysian Institute of Road Safety Research, 2018)
This study is to determine the travel mode for the trip to school by primary survey method at 30 primary schools in Selangor. This study approaching parents via student as a child and student. The method was more effective and additionally quality information was obtained. This study aimed to improve the quality of information on exposure travel to school among the student. In this study, mode travel was selected as the main variables for mode choice study. A total of 2508 parents were participated in this survey. The result shows that, the parents of younger children usually choose the motor vehicle as the main transport because their child being under adult supervising. This study found that the gender of the children was not an influence the mode choice to school. 46.2% of the student live less than 3km from school and 46% of parents choose motorcars as the main travel mode for their children. But the analysis shows that they tend to choose “walk” mode when travel distance is less than 1km. Although, the motorcar is the popular travel mode to school, there are some children walk/bicycle to school for less than 5km. The authorities need to strategize the development of facilities near the school. The travel mode choice helps the authorities build a better environment for student and community. It can reduce the risk exposure between home and school and develop safe routes to school. It can contribute information to better design policies and infrastructure around the school area.